Sweet Potato (Ipomoea batatas L.) Phenotypes: From Agroindustry to Health Effects - Alberto A. Escobar-Puentes; Iván Palomo; Lyanne Rodríguez; Eduardo Fuentes; Mónica A. Villegas-Ochoa; Gustavo A. González-Aguilar; Francisco J. Olivas-Aguirre; Abraham Wall-Medrano (Foods, 2022)
Sweet potato (SP; Ipomoea batatas (L.) Lam) is an edible tuber native to America and the sixth most important food crop worldwide. China leads its production in a global market of USD 45 trillion. SP domesticated varieties differ in specific phenotypic/genotypic traits, yet all of them are rich in sugars, slow digestible/resistant starch, vitamins, minerals, bioactive proteins and lipids, carotenoids, polyphenols, ascorbic acid, alkaloids, coumarins, and saponins, in a genotype-dependent manner. Individually or synergistically, SP’s phytochemicals help to prevent many illnesses, including certain types of cancers and cardiovascular disorders. These and other topics, including the production and market diversification of raw SP and its products, and SP’s starch as a functional ingredient, are briefly discussed in this review.